Demographic changes over >70 yr in a population of saguaro cacti (Carnegiea gigantea) in the northern Sonoran Desert. (April 2017) - Conver, Joshua L.; Foley, Theresa; Winkler, Daniel E.; Swann, Don E.
Abstract: We studied changes in a population of saguaro ( Carnegiea gigantea) cacti on a 259 ha plot in the northern Sonoran Desert (Saguaro National Park) that was first surveyed in 1941. With the help of citizen scientists, we mapped and measured the height of all detected individual saguaros. The total number of detected saguaros was 13, 304 in 1941 and 9023 in 2012, a 31.4% decrease. The population in 1941 consisted of mostly larger, older individuals, whereas in 2012 it was dominated by smaller, younger individuals. Based on estimated years of saguaro establishment, a period of high establishment in the mid-late 1800s was followed by many decades of poor establishment. However, establishment surged from the 1970s to early 1990s but has been very low since. Comparisons with other long-term saguaro studies suggest that the dramatic demographic changes in this area have resulted from climatic factors, most notably recent long-term drought and higher temperatures, in combination with land-use changes, especially loss of nurse trees due to wood-cutting early in the twentieth century. Highlights: Intensive wood-cutting and grazing prevented saguaro establishment in the early 1900s. Saguaro establishment surged from 1960-1990 due to recovery of nurse plants and favorable climate. Establishment since the mid-1990s has been low. The population was dominated by mature adult saguaros in 1941 and by juveniles in 2012. We observed a 31.4% decrease in the number of saguaros from 1941 to 2012.